Postmemorial Positions: Reading and Writing After the Holocaust in Anne Michaels’s Fugitive Pieces - Grimwood, Marita (Canadian Jewish Studies / Études juives canadiennes, 2003)
Anne Michaels’s novel, Fugitive Pieces, has been criticized for its highly poeticized representation of the Holocaust. In this essay, however, Marita Grimwood argues that the novel uses structures of narrative transmission to explore precisely the difficulties of representing history and trauma in language. Grimwood proposes that the representation of three key characters is central to this undertaking. First, Jakob Beer, the child survivor and poet who narrates two thirds of the novel, is positioned as an intergenerational mediator, belonging fully neither to a pre-war nor a postwar generation. Two further characters (Ben, the child of survivors who narrates the end of the novel, and Michaela, Jakob’s second wife) symbolize the figure of the reader after the Holocaust, negotiating a link to the past through their interpretation and witnessing of Jakob’s life. The novel recognizes the problems inherent in communicating meaningful knowledge of past events to those living in the present. Yet, partly through Jakob’s vocation as a poet, it proposes also that poetry is a tool, however imperfect, for the communication of such knowledge.